A lithium cobalt oxide positive electrode sheet and a lithium battery prepared therefrom

By adding polydopamine-coated carbon black, silica-polyester composite and polyester binder to the cathode slurry of the lithium cobalt oxide cathode sheet, the capacity fading of the lithium cobalt oxide cathode sheet during the charge and discharge process is solved. problems, improving the cycle capacity retention rate, energy density and safety of lithium batteries.

CN118645591BActive Publication Date: 2025-01-21NANJING HANRUI NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410868069.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-01-21
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

Traditional lithium cobalt oxide positive electrode sheets have capacity attenuation problems during charging and discharging, which affects the performance and life of the battery.

Method used

By adding polydopamine-coated carbon black, silica-polyester composite and polyester binder to the cathode slurry, a cathode material with high conductivity and mechanical strength is formed, which improves the cycle capacity retention rate of the battery. and energy density.

Benefits of technology

It effectively improves the cycle capacity retention rate, energy density and safety of lithium batteries, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion batteries, and specifically to a lithium cobalt oxide positive electrode sheet and a lithium battery prepared therefrom. The present invention adds polydopamine-coated carbon black, a silica-polyester composite and a polyester binder to the positive electrode slurry, which can effectively improve the battery cycle capacity retention rate, and improve the energy density and safety of the battery. The present invention increases the diffusion coefficient of lithium ions and improves the cycle performance of the lithium cobalt oxide positive electrode charge and discharge by coating polydopamine on the surface of carbon black. The present invention also prepares a polyester having a large number of carboxyl groups at the end group, and then forms silica nanoparticles in situ in the polyester by adding tetraethyl orthosilicate. Compared with adding silica nanoparticles alone to the positive electrode slurry and then dispersing them, the silica nanoparticles of the present invention have better dispersibility and are not easy to agglomerate, and the polyester binder and the silica-polyester composite have excellent compatibility, which enhances the lithium battery cycle capacity retention rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium cobalt oxide positive electrode sheet and a lithium battery prepared using the same. Background Art

[0002] With the rapid development of renewable energy and electric vehicles, lithium-ion batteries, as a type of battery with high energy density and long life, have received extensive attention and application. As one of the important components of lithium-ion batteries, the performance of the positive electrode directly affects the energy density, cycle stability and safety of the battery.

[0003] As one of the positive electrode materials, lithium cobalt oxide has high specific capacity and cycle stability in lithium-ion batteries, so it is widely used in electric vehicles, portable electronic products and other fields. However, the traditional lithium cobalt oxide positive electrode has the problem of capacity decay during the charging and discharging process, which affects the performance and life of the battery.

[0004] In order to solve the above problems and improve the battery cycle capacity retention rate, the present invention provides a lithium cobalt oxide positive electrode sheet and a lithium battery prepared therefrom. Summary of the invention

[0005] The object of the present invention is to provide a lithium cobalt oxide positive electrode sheet and a lithium battery prepared therefrom, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a lithium cobalt oxide positive electrode sheet comprises the following steps:

[0008] Step 1: Take carboxylated polyester, tetraethyl orthosilicate, and deionized water, heat to 50-55°C, stir for 2-3 hours, then drop triethanolamine to adjust the pH value to 8-8.3, cool to 25-30°C, stir for 11-13 hours, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite;

[0009] Step 2: Take polyester binder and N-methylpyrrolidone, stir evenly, add silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and N-methylpyrrolidone, stir for 3-4 hours, and obtain positive electrode slurry;

[0010] Step 3: Apply the positive electrode slurry on both sides of the aluminum foil and dry it at 100-110°C to obtain a lithium cobalt oxide positive electrode sheet.

[0011] More optimally, the positive electrode slurry includes the following components, calculated by weight: 95-100 parts of lithium cobalt oxide powder, 20-25 parts of N-methylpyrrolidone, 4-5 parts of amino carbon black, 3-4 parts of polyester binder, and 2-3 parts of silica-polyester composite.

[0012] More optimally, the preparation method of the carboxylated polyester is: take 1,2,4-trimethylbenzene anhydride and tetrahydrofuran, stir evenly, add polyethylene glycol and p-toluenesulfonic acid, stir for 6-7 hours under nitrogen protection, heat to 110-120°C, react for 2-3 hours, add N,N-dimethylformamide, heat at 135-140°C for 6-7 hours, dialyze, then soak with acetone, dialyze, and dry to obtain the carboxylated polyester.

[0013] More optimally, the preparation method of the polyester binder is: take 1,3-propylene glycol, 2,3-butanediol, itaconic acid, succinic acid, sebacic acid, antioxidant phosphorous acid, and hydroquinone, and under nitrogen protection, heat to 175-180°C, react for 2-3h, then cool to 100-102°C, add catalyst tetrabutyl titanate and inhibitor 2-tert-butylhydroquinone, heat to 220-225°C, react for 5-7h, cool to 60-65°C, wash, precipitate, and dry to obtain a polyester binder.

[0014] More optimally, the preparation method of the amination carbon black is: take carbon black and dopamine, add them into a tris buffer solution with a pH value of 8-8.5, and react for 22-24 hours to obtain the amination carbon black.

[0015] More optimally, the preparation method of the lithium cobalt oxide powder is: take lithium carbonate and cobalt oxide, ball mill, sinter at 950-960°C for 18-20h, and the heating rate is 4-5°C / min. After sintering, cool to 25-30°C, crush and sieve to obtain lithium cobalt oxide powder.

[0016] More optimally, the particle size of the lithium cobalt oxide powder is 6-8µm.

[0017] More optimally, the mass ratio of the carboxylated polyester to tetraethyl orthosilicate is 1:(1.1-1.3).

[0018] A lithium cobalt oxide positive electrode sheet prepared by a method for preparing a lithium cobalt oxide positive electrode sheet.

[0019] A lithium battery comprises a lithium cobalt oxide positive electrode sheet.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] (1) In the present invention, the addition of polydopamine-coated carbon black, silica-polyester composite and polyester binder to the positive electrode slurry can effectively improve the battery cycle capacity retention rate, improve the battery energy density and safety.

[0022] The present invention adds carbon black to the positive electrode slurry, effectively enhancing the conductivity and mechanical strength of the positive electrode material, and improving the energy density and cycle life of the battery. The present invention coats the carbon black surface with polydopamine, so that the carbon black surface has amino groups. The coating of polydopamine can promote the conduction of lithium ions, increase the diffusion coefficient of lithium ions, and improve the cycle performance of the cobalt oxide lithium positive electrode charge and discharge.

[0023] (2) The present invention uses 1,3-propylene glycol, 2,3-butanediol, itaconic acid, succinic acid, and sebacic acid as monomers to prepare a polyester binder, which is added to the positive electrode slurry as a binder. The binder has a large number of carboxyl and hydroxyl groups and has good adhesion. It can firmly fix lithium cobalt oxide particles and prevent particle shedding and structural damage, thereby improving the cycle life of the battery.

[0024] (3) The present invention uses 1,2,4-benzene trimellitic anhydride and polyethylene glycol to prepare a polyester having a large number of carboxyl groups at the end, and then forms silica nanoparticles in situ in the polyester by adding tetraethyl orthosilicate. Compared with adding silica nanoparticles alone to the positive electrode slurry and then dispersing them, the silica nanoparticles of the present invention have better dispersibility and are not easy to agglomerate. In addition, the polyester binder and the silica-polyester composite have excellent compatibility, thereby enhancing the cycle capacity retention rate of the lithium battery. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] There are no special restrictions on the purchase of all raw materials involved in the present invention, and exemplary manufacturers include:

[0027] Carbon black: particle size 100-200 nm; polyethylene glycol: PEG 600, model: 60361ES76, can be purchased from Yisheng Biotechnology Co., Ltd.

[0028] Embodiment 1: A method for preparing a lithium cobalt oxide positive electrode sheet, comprising the following steps:

[0029] Step 1: Preparation of lithium cobalt oxide powder:

[0030] Take 73g lithium carbonate and 150g cobalt oxide, ball mill, sinter at 950℃ for 19h, heating rate is 4℃ / min, cool to 28℃ after sintering, crush and sieve to obtain lithium cobalt oxide powder with a particle size of 6µm;

[0031] Step 2: Preparation of polyester binder:

[0032] Take 20g 1,3-propylene glycol, 25g 2,3-butanediol, 6.5g itaconic acid, 27g succinic acid, 45g sebacic acid, 5g antioxidant phosphorous acid, 1.2g hydroquinone, under nitrogen protection, heat to 177°C, react for 2.5h, then cool to 101°C, add 12g catalyst tetrabutyl titanate, 12g inhibitor 2-tert-butylhydroquinone, heat to 223°C, react for 6h, cool to 63°C, wash, precipitate, and dry to obtain a polyester binder;

[0033] Step 3: Preparation of carboxylated polyester:

[0034] Take 40g of 1,2,4-trimethylbenzene anhydride and 100mL of tetrahydrofuran, stir evenly, add 120g of polyethylene glycol and 2g of p-toluenesulfonic acid, stir for 6.5h under nitrogen protection, heat to 115°C, react for 2.5h, add 60mL of N,N-dimethylformamide, heat at 138°C for 6.5h, dialyze, then soak with acetone, dialyze, and dry to obtain carboxylated polyester;

[0035] Step 4: Preparation of silica-polyester composite:

[0036] Take 10g of carboxylated polyester, 12g of tetraethyl orthosilicate, and 100mL of deionized water, heat to 53°C, stir for 2.5h, then drop triethanolamine, adjust the pH value to 8, cool to 28°C, stir for 12h, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite;

[0037] The mass ratio of carboxylated polyester and tetraethyl orthosilicate is 1:1.2;

[0038] Step 5: Preparation of amination carbon black:

[0039] Take 5g of carbon black and 1g of dopamine, add them into a tris buffer solution with a pH value of 8.5, and react for 23h to obtain amino carbon black;

[0040] Step 6: Preparation of lithium cobalt oxide positive electrode:

[0041] Take a polyester binder and N-methylpyrrolidone accounting for one third of the total mass, stir evenly, add a silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and the remaining two thirds of N-methylpyrrolidone by mass, stir for 3.5 hours, and obtain a positive electrode slurry; apply the positive electrode slurry on both sides of the aluminum foil so that the positive electrode slurry coating thickness is 100 microns, and dry at 105°C to obtain a lithium cobalt oxide positive electrode sheet;

[0042] The positive electrode slurry includes the following components, calculated by weight: 98 parts of lithium cobalt oxide powder, 23 parts of N-methylpyrrolidone, 4.5 parts of amino carbon black, 3.5 parts of polyester binder, and 2.5 parts of silicon dioxide-polyester composite.

[0043] Embodiment 2: A method for preparing a lithium cobalt oxide positive electrode sheet, comprising the following steps:

[0044] Step 1: Preparation of lithium cobalt oxide powder:

[0045] Take 73g lithium carbonate and 150g cobalt oxide, ball mill, sinter at 950℃ for 18h, heating rate is 4℃ / min, cool to 25℃ after sintering, crush and sieve to obtain lithium cobalt oxide powder with a particle size of 6µm;

[0046] Step 2: Preparation of polyester binder:

[0047] Take 20g 1,3-propylene glycol, 25g 2,3-butanediol, 6.5g itaconic acid, 27g succinic acid, 45g sebacic acid, 5g antioxidant phosphorous acid, 1.2g hydroquinone, under nitrogen protection, heat to 175°C, react for 2h, then cool to 100°C, add 12g catalyst tetrabutyl titanate, 12g inhibitor 2-tert-butylhydroquinone, heat to 220°C, react for 5h, cool to 60°C, wash, precipitate, and dry to obtain a polyester binder;

[0048] Step 3: Preparation of carboxylated polyester:

[0049] Take 40g of 1,2,4-trimethylbenzene anhydride and 100mL of tetrahydrofuran, stir evenly, add 120g of polyethylene glycol and 2g of p-toluenesulfonic acid, stir for 6h under nitrogen protection, heat to 110°C, react for 2h, add 60mL of N,N-dimethylformamide, heat at 135°C for 6h, dialyze, then soak with acetone, dialyze, and dry to obtain carboxylated polyester;

[0050] Step 4: Preparation of silica-polyester composite:

[0051] Take 10g of carboxylated polyester, 11g of tetraethyl orthosilicate, and 100mL of deionized water, heat to 50°C, stir for 2h, then drop triethanolamine, adjust the pH value to 8, cool to 25°C, stir for 11h, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite;

[0052] The mass ratio of carboxylated polyester and tetraethyl orthosilicate is 1:1.1;

[0053] Step 5: Preparation of amination carbon black:

[0054] Take 5g of carbon black and 1g of dopamine, add them into a tris buffer solution with a pH value of 8.5, and react for 22h to obtain amino carbon black;

[0055] Step 6: Preparation of lithium cobalt oxide positive electrode:

[0056] Take a polyester binder and N-methylpyrrolidone accounting for one third of the total mass, stir evenly, add a silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and the remaining two thirds of N-methylpyrrolidone by mass, stir for 3 hours, and obtain a positive electrode slurry; apply the positive electrode slurry on both sides of an aluminum foil so that the coating thickness of the positive electrode slurry is 100 microns, and dry at 100° C. to obtain a lithium cobalt oxide positive electrode sheet;

[0057] The positive electrode slurry includes the following components, calculated by weight: 95 parts of lithium cobalt oxide powder, 20 parts of N-methylpyrrolidone, 4 parts of amino carbon black, 3 parts of polyester binder, and 2 parts of silicon dioxide-polyester composite.

[0058] Embodiment 3: A method for preparing a lithium cobalt oxide positive electrode sheet, comprising the following steps:

[0059] Step 1: Preparation of lithium cobalt oxide powder:

[0060] Take 73g lithium carbonate and 150g cobalt oxide, ball mill, sinter at 960℃ for 20h, heating rate is 5℃ / min, cool to 30℃ after sintering, crush and sieve to obtain lithium cobalt oxide powder with a particle size of 6µm;

[0061] Step 2: Preparation of polyester binder:

[0062] Take 20g 1,3-propylene glycol, 25g 2,3-butanediol, 6.5g itaconic acid, 27g succinic acid, 45g sebacic acid, 5g antioxidant phosphorous acid, 1.2g hydroquinone, under nitrogen protection, heat to 180°C, react for 3h, then cool to 102°C, add 12g catalyst tetrabutyl titanate, 12g inhibitor 2-tert-butylhydroquinone, heat to 225°C, react for 7h, cool to 65°C, wash, precipitate, and dry to obtain a polyester binder;

[0063] Step 3: Preparation of carboxylated polyester:

[0064] Take 40g of 1,2,4-trimethylbenzene anhydride and 100mL of tetrahydrofuran, stir evenly, add 120g of polyethylene glycol and 2g of p-toluenesulfonic acid, stir for 7h under nitrogen protection, heat to 120°C, react for 3h, add 60mL of N,N-dimethylformamide, heat at 140°C for 7h, dialyze, then soak with acetone, dialyze, and dry to obtain carboxylated polyester;

[0065] Step 4: Preparation of silica-polyester composite:

[0066] Take 10g of carboxylated polyester, 13g of tetraethyl orthosilicate, and 100mL of deionized water, heat to 55°C, stir for 3h, then drop triethanolamine, adjust the pH value to 8.3, cool to 30°C, stir for 13h, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite;

[0067] The mass ratio of carboxylated polyester to tetraethyl orthosilicate is 1:1.3;

[0068] Step 5: Preparation of amination carbon black:

[0069] Take 5g of carbon black and 1g of dopamine, add them into a tris buffer solution with a pH value of 8.5, and react for 24h to obtain amino carbon black;

[0070] Step 6: Preparation of lithium cobalt oxide positive electrode:

[0071] Take a polyester binder and N-methylpyrrolidone accounting for one third of the total mass, stir evenly, add a silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and the remaining two thirds of N-methylpyrrolidone by mass, stir for 4 hours, and obtain a positive electrode slurry; apply the positive electrode slurry on both sides of the aluminum foil so that the positive electrode slurry coating thickness is 100 microns, and dry at 110°C to obtain a lithium cobalt oxide positive electrode sheet;

[0072] The positive electrode slurry includes the following components, calculated by weight: 100 parts of lithium cobalt oxide powder, 25 parts of N-methylpyrrolidone, 5 parts of amino carbon black, 4 parts of polyester binder, and 3 parts of silicon dioxide-polyester composite.

[0073] Comparative Example 1: Adding silica nanoparticles instead of silica-polyester composite, the rest is the same as Example 1:

[0074] Step 1: Preparation of lithium cobalt oxide powder:

[0075] Take 73g lithium carbonate and 150g cobalt oxide, ball mill, sinter at 950℃ for 19h, heating rate is 4℃ / min, cool to 28℃ after sintering, crush and sieve to obtain lithium cobalt oxide powder with a particle size of 6µm;

[0076] Step 2: Preparation of polyester binder:

[0077] Take 20g 1,3-propylene glycol, 25g 2,3-butanediol, 6.5g itaconic acid, 27g succinic acid, 45g sebacic acid, 5g antioxidant phosphorous acid, 1.2g hydroquinone, under nitrogen protection, heat to 177°C, react for 2.5h, then cool to 101°C, add 12g catalyst tetrabutyl titanate, 12g inhibitor 2-tert-butylhydroquinone, heat to 223°C, react for 6h, cool to 63°C, wash, precipitate, and dry to obtain a polyester binder;

[0078] Step 3: Preparation of amination carbon black:

[0079] Take 5g of carbon black and 1g of dopamine, add them into a tris buffer solution with a pH value of 8.5, and react for 23h to obtain amino carbon black;

[0080] Step 4: Preparation of lithium cobalt oxide positive electrode:

[0081] Take a polyester binder and N-methylpyrrolidone accounting for one third of the total mass, stir evenly, add silicon dioxide, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and the remaining two thirds of N-methylpyrrolidone by mass, stir for 3.5 hours, and obtain a positive electrode slurry; apply the positive electrode slurry on both sides of the aluminum foil so that the coating thickness of the positive electrode slurry is 100 microns, and dry at 105°C to obtain a lithium cobalt oxide positive electrode sheet;

[0082] The particle size of silicon dioxide is 10-20nm;

[0083] The positive electrode slurry includes the following components, calculated by weight: 98 parts of lithium cobalt oxide powder, 23 parts of N-methylpyrrolidone, 4.5 parts of amino carbon black, 3.5 parts of polyester binder, and 2.5 parts of silicon dioxide.

[0084] Comparative Example 2: The mass ratio of carboxylated polyester to tetraethyl orthosilicate is 1:0.6, and the rest is the same as Example 1:

[0085] Step 1: Preparation of lithium cobalt oxide powder:

[0086] Take 73g lithium carbonate and 150g cobalt oxide, ball mill, sinter at 950℃ for 19h, heating rate is 4℃ / min, cool to 28℃ after sintering, crush and sieve to obtain lithium cobalt oxide powder with a particle size of 6µm;

[0087] Step 2: Preparation of polyester binder:

[0088] Take 20g 1,3-propylene glycol, 25g 2,3-butanediol, 6.5g itaconic acid, 27g succinic acid, 45g sebacic acid, 5g antioxidant phosphorous acid, 1.2g hydroquinone, under nitrogen protection, heat to 177°C, react for 2.5h, then cool to 101°C, add 12g catalyst tetrabutyl titanate, 12g inhibitor 2-tert-butylhydroquinone, heat to 223°C, react for 6h, cool to 63°C, wash, precipitate, and dry to obtain a polyester binder;

[0089] Step 3: Preparation of carboxylated polyester:

[0090] Take 40g of 1,2,4-trimethylbenzene anhydride and 100mL of tetrahydrofuran, stir evenly, add 120g of polyethylene glycol and 2g of p-toluenesulfonic acid, stir for 6.5h under nitrogen protection, heat to 115°C, react for 2.5h, add 60mL of N,N-dimethylformamide, heat at 138°C for 6.5h, dialyze, then soak with acetone, dialyze, and dry to obtain carboxylated polyester;

[0091] Step 4: Preparation of silica-polyester composite:

[0092] Take 10g of carboxylated polyester, 6g of tetraethyl orthosilicate, and 100mL of deionized water, heat to 53°C, stir for 2.5h, then drop triethanolamine, adjust the pH value to 8, cool to 28°C, stir for 12h, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite;

[0093] The mass ratio of carboxylated polyester to tetraethyl orthosilicate is 1:0.6;

[0094] Step 5: Preparation of amination carbon black:

[0095] Take 5g of carbon black and 1g of dopamine, add them into a tris buffer solution with a pH value of 8.5, and react for 23h to obtain amino carbon black;

[0096] Step 6: Preparation of lithium cobalt oxide positive electrode:

[0097] Take a polyester binder and N-methylpyrrolidone accounting for one third of the total mass, stir evenly, add a silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and the remaining two thirds of N-methylpyrrolidone by mass, stir for 3.5 hours, and obtain a positive electrode slurry; apply the positive electrode slurry on both sides of the aluminum foil so that the positive electrode slurry coating thickness is 100 microns, and dry at 105°C to obtain a lithium cobalt oxide positive electrode sheet;

[0098] The positive electrode slurry includes the following components, calculated by weight: 98 parts of lithium cobalt oxide powder, 23 parts of N-methylpyrrolidone, 4.5 parts of amino carbon black, 3.5 parts of polyester binder, and 2.5 parts of silicon dioxide-polyester composite.

[0099] Comparative Example 3: Polydopamine is not used to coat carbon black, and the rest is the same as Example 1:

[0100] Step 1: Preparation of lithium cobalt oxide powder:

[0101] Take 73g lithium carbonate and 150g cobalt oxide, ball mill, sinter at 950℃ for 19h, heating rate is 4℃ / min, cool to 28℃ after sintering, crush and sieve to obtain lithium cobalt oxide powder with a particle size of 6µm;

[0102] Step 2: Preparation of polyester binder:

[0103] Take 20g 1,3-propylene glycol, 25g 2,3-butanediol, 6.5g itaconic acid, 27g succinic acid, 45g sebacic acid, 5g antioxidant phosphorous acid, 1.2g hydroquinone, under nitrogen protection, heat to 177°C, react for 2.5h, then cool to 101°C, add 12g catalyst tetrabutyl titanate, 12g inhibitor 2-tert-butylhydroquinone, heat to 223°C, react for 6h, cool to 63°C, wash, precipitate, and dry to obtain a polyester binder;

[0104] Step 3: Preparation of carboxylated polyester:

[0105] Take 40g of 1,2,4-trimethylbenzene anhydride and 100mL of tetrahydrofuran, stir evenly, add 120g of polyethylene glycol and 2g of p-toluenesulfonic acid, stir for 6.5h under nitrogen protection, heat to 115°C, react for 2.5h, add 60mL of N,N-dimethylformamide, heat at 138°C for 6.5h, dialyze, then soak with acetone, dialyze, and dry to obtain carboxylated polyester;

[0106] Step 4: Preparation of silica-polyester composite:

[0107] Take 10g of carboxylated polyester, 12g of tetraethyl orthosilicate, and 100mL of deionized water, heat to 53°C, stir for 2.5h, then drop triethanolamine, adjust the pH value to 8, cool to 28°C, stir for 12h, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite;

[0108] The mass ratio of carboxylated polyester and tetraethyl orthosilicate is 1:1.2;

[0109] Step 5: Preparation of lithium cobalt oxide positive electrode:

[0110] Take a polyester binder and N-methylpyrrolidone accounting for one third of the total mass, stir evenly, add a silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and the remaining two thirds of N-methylpyrrolidone by mass, stir for 3.5 hours, and obtain a positive electrode slurry; apply the positive electrode slurry on both sides of the aluminum foil so that the positive electrode slurry coating thickness is 100 microns, and dry at 105°C to obtain a lithium cobalt oxide positive electrode sheet;

[0111] The positive electrode slurry includes the following components, calculated by weight: 98 parts of lithium cobalt oxide powder, 23 parts of N-methylpyrrolidone, 4.5 parts of carbon black, 3.5 parts of polyester binder, and 2.5 parts of silicon dioxide-polyester composite.

[0112] experiment:

[0113] Take 2g of sodium carboxymethyl cellulose, 5g of carboxylated styrene butadiene rubber, 98g of graphite with a particle size of 40-50nm, 3g of carbon black, and 25g of deionized water, stir evenly to obtain a negative electrode slurry; evenly coat the negative electrode slurry on both sides of the copper foil with a coating thickness of 100µm, and dry to obtain a negative electrode sheet; adopt the lithium cobalt oxide positive electrode sheet prepared in Example 1-3 and Comparative Example 1-3; wind the negative electrode sheet and the lithium cobalt oxide positive electrode sheet into a 18650 cylindrical battery, then dry at 100°C for 24h, inject 5.2g of LD-88 electrolyte, seal, and stand for 12 hours to obtain a lithium battery; then charge to 4.4 at 25°C at a constant current and constant voltage of 1.5C. 8V, let it stand for 5 minutes, then use 0.7C constant current to discharge to 3.0V, let it stand for 5 minutes, cycle charge and discharge 800 times, and test the cycle performance of the battery at room temperature; then at 45℃, charge to 4.48V at 1.5C constant current and constant voltage, let it stand for 5 minutes, then use 0.7C constant current to discharge to 3.0V, let it stand for 5 minutes, cycle charge and discharge 800 times, and test the cycle performance of the battery at 45℃; perform thermal shock test on lithium batteries. After the lithium batteries are fully charged according to the standard method, they are placed in a temperature control box. The box is heated at a rate of 5℃ / min and placed at a constant temperature of 130℃ for 1h to observe the lithium state. The data obtained are shown in the following table:

[0114]

[0115] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, silica nanoparticles are added instead of silica-polyester composites, and the silica nanoparticles are easy to agglomerate, which affects the cycle capacity retention rate of the lithium battery. In Comparative Example 2, the mass ratio of carboxylated polyester and tetraethyl orthosilicate is 1:0.6, the amount of silica added is reduced, and the cycle life of the battery is deteriorated. In Example 1-3, a polyester with a large number of carboxyl groups at the end is prepared using 1,2,4-benzene trimellitic anhydride and polyethylene glycol, and then tetraethyl orthosilicate is added to form silica nanoparticles in situ in the polyester. Compared with adding silica nanoparticles alone to the positive electrode slurry and then dispersing them, the silica nanoparticles of the present invention have better dispersibility, are not easy to agglomerate, and the polyester binder and silica-polyester composite have excellent compatibility, and the lithium battery cycle capacity retention rate is high. In Comparative Example 3, polydopamine is not used to coat carbon black, and the dispersibility of carbon black is deteriorated, which affects the cycle life of the battery. In Example 1-3, polydopamine is coated on the surface of carbon black to make the surface of carbon black have amino groups. The coating of polydopamine can promote the conduction of lithium ions, increase the diffusion coefficient of lithium ions, and improve the cycle performance of the cobalt oxide positive electrode charge and discharge. The lithium battery prepared by the scheme provided by Example 1-3 of the present invention has a high cycle capacity retention rate and good safety.

[0116] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium cobalt oxide positive electrode sheet, characterized in that: The following steps are involved: Step 1: Take carboxylated polyester, tetraethyl orthosilicate, and deionized water, heat to 50-55°C, stir for 2-3 hours, then drop triethanolamine to adjust the pH value to 8-8.3, cool to 25-30°C, stir for 11-13 hours, dialyze, then soak with deionized water, and dry to obtain a silica-polyester composite; Step 2: Take polyester binder and N-methylpyrrolidone, stir evenly, add silica-polyester composite, stir evenly, add amino carbon black, stir evenly, then add lithium cobalt oxide powder and N-methylpyrrolidone, stir for 3-4 hours, and obtain positive electrode slurry; Step 3: coating the positive electrode slurry on both sides of the aluminum foil and drying at 100-110° C. to obtain a lithium cobalt oxide positive electrode sheet; The preparation method of the polyester binder is as follows: 1,3-propylene glycol, 2,3-butanediol, itaconic acid, succinic acid, sebacic acid, antioxidant phosphorous acid, and hydroquinone are taken, heated to 175-180° C. under nitrogen protection, reacted for 2-3 hours, then cooled to 100-102° C., tetrabutyl titanate catalyst and 2-tert-butyl hydroquinone inhibitor are added, heated to 220-225° C., reacted for 5-7 hours, cooled to 60-65° C., washed, precipitated, and dried to obtain the polyester binder; The preparation method of the amination carbon black is as follows: carbon black and dopamine are added into a tris buffer solution with a pH value of 8-8.5, and reacted for 22-24 hours to obtain the amination carbon black.

2. The method for preparing a lithium cobalt oxide positive electrode sheet according to claim 1, characterized in that: The positive electrode slurry comprises the following components, calculated by weight: 95-100 parts of lithium cobalt oxide powder, 20-25 parts of N-methylpyrrolidone, 4-5 parts of amino carbon black, 3-4 parts of polyester binder, and 2-3 parts of silicon dioxide-polyester composite.

3. The method for preparing a lithium cobalt oxide positive electrode sheet according to claim 1, characterized in that: The preparation method of the carboxylated polyester is as follows: 1,2,4-trimellitic anhydride and tetrahydrofuran are taken, stirred evenly, polyethylene glycol and p-toluenesulfonic acid are added, stirred for 6-7 hours under nitrogen protection, heated to 110-120° C., reacted for 2-3 hours, N,N-dimethylformamide is added, heated at 135-140° C. for 6-7 hours, dialyzed, then soaked in acetone, dialyzed, and dried to obtain the carboxylated polyester.

4. The method for preparing a lithium cobalt oxide positive electrode sheet according to claim 2, characterized in that: The preparation method of the lithium cobalt oxide powder is as follows: lithium carbonate and cobalt oxide are taken, ball-milled, sintered at 950-960° C. for 18-20 hours, with a heating rate of 4-5° C. / min, cooled to 25-30° C. after sintering, crushed and sieved to obtain the lithium cobalt oxide powder.

5. The method for preparing a lithium cobalt oxide positive electrode sheet according to claim 4, characterized in that: The particle size of the lithium cobalt oxide powder is 6-8 μm.

6. The method for preparing a lithium cobalt oxide positive electrode sheet according to claim 1, characterized in that: The mass ratio of the carboxylated polyester to tetraethyl orthosilicate is 1:(1.1-1.3).

7. A lithium cobalt oxide positive electrode sheet prepared according to the method for preparing a lithium cobalt oxide positive electrode sheet according to any one of claims 1 to 6.

8. A lithium battery, characterized in that: The lithium battery comprises the lithium cobalt oxide positive electrode sheet as claimed in claim 7.

Citation Information

Patent Citations

  • Multifunctional integrated composite electrode slurry material containing active carbonyl polymer and preparation method of slurry material

    CN109411761A

  • Water-based binder for lithium-sulfur battery and preparation method of water-based binder

    CN111106353A